Climate Change and the German Law of Torts - Semmelmayer, Philipp (German Law Journal, 2021)
Even throughout a global pandemic, climate change continues to be a fiercely discussed topic-both politically and legally-the world over. Particularly in light of the many Covid-19 related financial aid programs (including transnational ones) and the associated economic stabilization and reconstruction plans, a sustainable climate policy and legal order should be expected to play a role for an economy that has fallen into a slump. Nevertheless, a lively discussion on how best to achieve climate protection continues to take place in already established systems such as the private law system. Here, as far as climate change is concerned, tort law appears to be the focus of these discussions. The extent to which tort law and the issue of climate change can be brought together is also increasingly being discussed in Germany. This article attempts to shed light on the questions of how tort law could contribute to the mitigation of climate change and how climate change could fit into the law of torts of the German civil law legal system.
CRIS-Team WoS Importer:2022-02-11

Climate Change and Torts: New Zealand and Germany - Semmelmayer, Philipp (Comparative Law Journal of the Pacific - Journal de Droit Comparé du Pacifique, 2021)

Kommanditgesellschaftsrecht im Nationalsozialismus - Semmelmayer, Philipp (Mohr Siebeck, 2025)
hilipp Semmelmayer untersucht die jüngere Geschichte des Kommanditgesellschaftsrechts. Er legt dabei den Schwerpunkt auf die für die Kommanditgesellschaft bedeutende Zeit des Nationalsozialismus. In dieser Zeit galten die Personengesellschaften und insbesondere die Kommanditgesellschaft als förderungswürdiges Idealbild. Hingegen wurden die Kapitalgesellschaften verteufelt. Es kam zu einer „Flucht“ hinaus aus den Kapitalgesellschaften und hinein in die Kommanditgesellschaft. Diese Entwicklung resultierte in einer komplexen gesellschaftsvertraglichen Praxis, welche sich durch eine Anpassung des Kommanditgesellschaftsrechts an das Kapitalgesellschaftsrecht auszeichnete. In der Folge kam es zu Diskussionen in der Wissenschaft, vor den Gerichten und auf ministerialer Ebene. Philipp Semmelmayer bringt diese Diskussionen mitsamt ihrer Protagonisten ans Lic

Rezension: Clara Günzl, Eine andere Geschichte der Begründungspflicht, Tübingen 2021 - Semmelmayer, Philipp (Zeitschrift für Neuere Rechtsgeschichte, 2022)

Rezension: Susanne Karoline Paas, Das bewegliche System, Tübingen 2021 - Semmelmayer, Philipp (Zeitschrift für Neuere Rechtsgeschichte, 2021)

The Climate Change Response (Zero Carbon) Amendment Act – A Critical Analysis of New Zealand`s Response to Climate Change - Semmelmayer, Philipp (New Zealand Journal of Environmental Law, 2020)

Übungsblätter Referendare: „Die missglückte Hauptverhandlung“ - Semmelmayer, Philipp; Semmelmayer, Lukas (Juristische Arbeitsblätter, 2022)